Secondary Mortgage Market And Asset Backed Securities In Malaysia - Wanyoike, Gachogu (2006)
The Malaysian secondary mortgage market has been dormant in the face of successful primary issues and despite being among the first in the region to venture into securitisation in an attempt to broaden the capital markets. The securities achieve good ratings while they are part of larger scheme by the government to provide affordable housing. The Malaysian investor does not seem to show a preference for these securities over similar rated AAA corporate issues.